24 Experiences of oldest-old carers whose partner is approaching end-of-life: a systematic review and narrative synthesis. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Morgan, Tessa; Bharmal, Aamena; Duschinsky, Robbie; Barclay, Stephen
Abstract : Background: Globally ageing populations have rapidly increased the number of people requiring palliative care. In resource-limited healthcare systems, spouses are increasingly providing end-of-life care to enable their partners to remain at home. Little attention, however, has been paid to oldest-old spousal carers who are often managing their own co-morbidities whilst caring. Aim: To review the literature concerning experiences of carers aged 75 and over whose partner is approaching end-of-life. Methods: Systematic review and narrative synthesis of the empirical literature published between 1985-April 2018 across six databases. Gough's weight of evidence and Morgan's feminist appraisal tool used to determine quality of papers. Results: From the initial 6950 titles, eight qualitative studies and six quantitative studies were included. Five studies focused exclusively on care recipients with severe dementia. We identified three themes. (1) 'The embodied impact of care'. Many oldest-old carers experienced a 'double jeopardy' while providing emotionally and physically difficult end-of-life care and managing their own diminishing health. They often subordinated their own health needs to continue caring. (2) 'Marital and gendered conceptualisations of caring'. Oldest-old carers strove for normality in their self and marriage identities by providing care for their spouse with little additional support and by incorporating their caregiving within their established gender roles. (3) 'Learning to care'. Oldest-old carers had to learn new skills and ways of coping to keep their spouses at home. They became the expert of their partners' condition as well as having to take over all household tasks. Conclusion: This review highlights the importance of oldest-old carers contributions to their spouses' end-of-life care. Oldest-old carers see it as their duty to care, but the caregiving itself involves learning new practical and emotional skills. Future research needs to consider how to best support these carers to do so without grave impact to their own health.